BUSINESS AVIATION IN EUROPE (Perner's Contacts, 2011)
Business Aviation remains unexplored and little attention is paid to its operation. This article is revealing some important facts about it and making a comparison with airlines´ traffic characteristics.
Keywords: Air Transportation; Airline; Airport; Business Aviation; Europe